Projektowanie systemu HRM w OGP Gaz-System Sp. Z o.o. Oddział Wrocław - próba oceny efektywności - Hnatio, Krzysztof (Designing the HRM System in Gaz-System Sp. z o.o. Division in Wrocław - the Attempt of Estimating the Effectiveness, 2006)
The paper attempts to estimate the assessment system introduced in Gaz-System Sp. z o.o. Division in Wroclaw as a tool increasing the effectiveness of human resources management.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1104, s. 482-488